2016
DOI: 10.1002/cphc.201601042
|View full text |Cite
|
Sign up to set email alerts
|

Libration of Strongly‐Oriented Polar Molecules inside a Superfluid

Abstract: We study a polar molecule immersed into a superfluid environment, such as a helium nanodroplet or a Bose-Einstein condensate, in the presence of an intense electrostatic field. We show that coupling of the molecular pendular motion, induced by the field, to the fluctuating bath leads to formation of pendulons -spherical harmonic librators dressed by a field of many-particle excitations. We study the behavior of the pendulon in a broad range of molecule-bath and molecule-field interaction strengths, and reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…As a result, a detailed quantum mechanical understanding of molecular impurities in helium requires first-principles approaches based on extensive numerical simulations [7]. During last years, several numerical studies, based mainly on pathintegral, variational, and diffusion quantum Monte-Carlo (MC), have been performed for molecules embedded in finite-size He n clusters with n 100 [22,.In this Letter we show that such an involved manyparticle problem simplifies tremendously, if one assumes that molecules in helium droplets form angulons -recently introduced quasiparticles consisting of a quantum rotor dressed by a field of many-body excitations [47][48][49][50][51][52][53][54]. The angulon theory is inherently many-body and describes interactions between a molecule and an infinite number of helium atoms.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…As a result, a detailed quantum mechanical understanding of molecular impurities in helium requires first-principles approaches based on extensive numerical simulations [7]. During last years, several numerical studies, based mainly on pathintegral, variational, and diffusion quantum Monte-Carlo (MC), have been performed for molecules embedded in finite-size He n clusters with n 100 [22,.In this Letter we show that such an involved manyparticle problem simplifies tremendously, if one assumes that molecules in helium droplets form angulons -recently introduced quasiparticles consisting of a quantum rotor dressed by a field of many-body excitations [47][48][49][50][51][52][53][54]. The angulon theory is inherently many-body and describes interactions between a molecule and an infinite number of helium atoms.…”
mentioning
confidence: 93%
“…In this Letter we show that such an involved manyparticle problem simplifies tremendously, if one assumes that molecules in helium droplets form angulons -recently introduced quasiparticles consisting of a quantum rotor dressed by a field of many-body excitations [47][48][49][50][51][52][53][54]. The angulon theory is inherently many-body and describes interactions between a molecule and an infinite number of helium atoms.…”
mentioning
confidence: 96%
“…Recently, it was shown that interaction of such orbital impurities with a many-particle environment can be rationalized by using the concept of the angulon quasiparticle [52][53][54][55][56][57][58]. While in the case of polarons the bath degrees of freedom couple to the impurity's translational motion, in angulons the orbital angular momentum is redistributed between the impurity and the many-particle environment.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of angulons has been used to study a variety of physical systems, ranging from molecular ions rotating in a BEC [61] to molecules in superfluid helium nanodroplets [55,57], using variational approaches in either the strong- [53,58] or weak-coupling [52,56,57] regimes. A strong evidence was provided that molecules rotating in superfluid 4 He form angulon quasiparticles [55,62].…”
Section: Introductionmentioning
confidence: 99%
“…The second term of Eq. (1), corresponds to the many-body part of the Hamiltonian, which includes the kinetic energy of the bath and the impurity-bath interactions that depend on r. Furthermore,Ĥ mb (r) can include any external potential such as that due to an electromagnetic field [53][54][55]. The eigenvalue equation for Hamiltonian (1) can be written asĤ (r)|Ψ α (r) = E α |Ψ α (r) ,where |Ψ α (r) ≡ r|Ψ α is the eigenstate in the coordinate space of the impurity, and α is the quantum number labeling the eigenstate.…”
mentioning
confidence: 99%